Preparation of neuroprotective condensed 1,4-benzoxazepines by regio- and diastereoselective domino Knoevenagel–[1,5]-hydride shift cyclization reaction - Tóth, László; Fu, Yan; Zhang, Hai Yan; Mándi, Attila; Kövér, Katalin E.; Illyés, Tünde-Zita; Kiss-Szikszai, Attila; Balogh, Balázs; Kurtán, Tibor; Antus, Sándor; Mátyus, Péter (Beilstein Journal of Organic Chemistry, 2014)
Condensed O,N-heterocycles containing tetrahydro-1,4-benzoxazepine and tetrahydroquinoline moieties were prepared by a regio- and diastereoselective domino Knoevenagel–[1,5]-hydride shift cyclization reaction of a 4-aryl-2-phenyl-1,4-benzoxazepine derivative obtained from flavanone. The relative configuration of products were determined by the correlation of 3JH,H coupling data with the geometry of major conformers accessed by DFT conformational analysis. Separated enantiomers of the products were characterized by HPLC-ECD data, which allowed their configurational assignment on the basis of TDDFT-ECD calculation of the solution conformers. Two compounds showed neuroprotective activities against hydrogen peroxide (H2O2) or β-amyloid25–35 (Aβ25–35)-induced cellular injuries in human neuroblastoma SH-SY5Y cells in the range of those of positive controls.
Keywords: 1,4-benzoxazepine; diastereoselective domino Knoevenagel–[1,5]-hydride shift cyclization; neuroprotective; tert-amino effect; TDDFT-ECD calculation